Method for improving thermal fatigue durability of nickel-titanium alloy

Through the twisting and untwist cycle of nickel-titanium alloy fibers, combined with copper foil and Kevlar fiber wrap, the problem of mechanical hysteresis and low fatigue resistance in elastic and thermal refrigeration is solved, and high-efficiency cooling and durability are achieved. The fiber reaches a higher number of cycles under high temperature differences.

CN119307842APending Publication Date: 2025-01-14CHINA PHARM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411285013.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the application of elastic-heat refrigeration, existing shape memory alloys have mechanical hysteresis and low cyclic fatigue resistance, making it difficult to achieve high elastic-heat performance, low hysteresis, low driving stress and long cycle life at the same time.

Method used

Ni-titanium alloy fibers are used, fixed by drill chuck and driven by stepper motors, twisting and untwist cycles are carried out, combined with copper foil and Kevlar fibers to improve the durability and heat transfer efficiency of the fibers.

Benefits of technology

High cooling efficiency and high durability are achieved, nonlinear stress gradient distribution is generated, crack generation and expansion is prevented, fatigue resistance is improved, and the fiber reaches 14,752 cycles at a temperature difference of 6K.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307842A_ABST
    Figure CN119307842A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving thermal fatigue durability of a nickel-titanium alloy. The method comprises the following steps: processing the nickel-titanium alloy into a fiber shape with the diameter of 0.4-1.0 mm; fixing two ends of the fiber by a drill chuck; and a stepping motor is connected with a fixed chuck to drive the nickel-titanium alloy fiber elastic heat so as to twist the nickel-titanium alloy fiber. By twisting the nickel-titanium alloy fibers, high cooling efficiency and high durability are achieved, and meanwhile needed stress input is low. The nickel-titanium alloy fibers are twisted to generate unique nonlinear stress gradient distribution, so that a periodic rigid-flexible structure is formed. A high-stress area shows large entropy change and temperature change, and a low-stress area shows high elastic recovery capacity, so that the energy efficiency ratio is large, and high efficiency is achieved. The twisting of the nickel-titanium alloy fibers can also prevent the generation and expansion of cracks, so that the combination of high elastic thermal performance and enhanced fatigue resistance is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to solid-state refrigeration technology, specifically focusing on the application of shape memory alloy solid-state refrigeration materials, and more particularly to an application method for increasing the elastic and thermal durability of nickel-titanium alloy fibers. Background Art

[0002] Shape memory alloys (SMAs), as a special material, have attracted widespread attention due to their unique shape memory effect and superelastic properties. They were first discovered by William Buehler and others at the U.S. Naval Research Laboratory in the 1960s, and their initial applications were mainly concentrated in the aerospace field. However, as time went on, around 1985, people began to realize that SMAs could be used in refrigeration systems, marking the beginning of elastocaloric refrigeration technology.

[0003] Applying uniaxial tensile stress to shape memory alloys (SMAs) is the most commonly used elasto-caloric cooling strategy. This results in a large temperature span, but this approach is accompanied by large mechanical hysteresis work due to lattice expansion and the generation and growth of dislocations and cracks, which in turn induces low cyclic fatigue resistance. In recent years, a lot of research has been devoted to reducing the hysteresis of SMAs and increasing their cycle life. In addition to stretching, different applications have been used to try to increase the elasto-caloric life, such as uniaxial compression and bending for elasto-caloric cooling, which suppress lattice expansion, dislocation slip and crack formation. However, it is difficult to achieve large temperature differences in SMAs under bending conditions because of their incomplete phase transformation, while under compression conditions, complex device designs with large driving forces are required to prevent buckling and achieve efficient heat transfer. Although significant results have been achieved, it remains a challenge to achieve SMAs with high elasto-caloric performance, low hysteresis, low driving stress and long cycle life. Summary of the invention

[0004] The present invention provides a method for improving the thermal fatigue durability of nickel-titanium alloy, and achieves high cooling efficiency and high durability by twisting nickel-titanium alloy fibers. In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is:

[0005] A method for improving the thermal fatigue durability of a nickel-titanium alloy projectile comprises the following steps:

[0006] (a) The nickel-titanium alloy used contains 51.3% nickel and 48.7% titanium by weight and is processed into a fiber shape with a diameter ranging from 0.4 mm to 1.0 mm;

[0007] (b) Use a drill chuck to fix both ends of the fiber;

[0008] (c) using a stepper motor connected to a fixed chuck to drive the nickel-titanium alloy fiber elastic heat;

[0009] Wherein step (b) is to wrap both ends of the fiber with 0.3 mm copper foil. If it is multiple strands, first wrap the nickel-titanium alloy fiber with copper foil, then wrap the copper foil with Kevlar fiber, and fix both ends to the drill chuck.

[0010] Furthermore, the austenite-martensite phase transition temperature of the nickel-titanium alloy is between -20 and 0°C, and the fiber length is between 3 and 30 cm.

[0011] Furthermore, when the drill chuck is used to clamp the nickel-titanium alloy fiber, a 0.3 mm copper foil is used to wrap the nickel-titanium alloy as a buffer layer at the contact point between the chuck and the nickel-titanium alloy.

[0012] Further, one of the drill chucks is fixed in a stable position, and the other drill chuck is coaxially connected to a stepping motor with a fixed length.

[0013] Furthermore, the steps of cyclic elastic heating are as follows: 1) controlling the stepper motor connected to the nickel-titanium alloy fiber material to twist it at a rate of 5-50 turns / s, so that the nickel-titanium alloy generates heat; 2) exchanging heat with the environment until it is close to the ambient temperature; 3) untwisting it at the same rate, so that the nickel-titanium alloy is cooled; 4) exchanging heat with the environment until it is close to the ambient temperature. The above steps realize the cyclic cooling and heating of the nickel-titanium alloy.

[0014] Furthermore, the twisted nickel-titanium alloy material also includes 2 to 5 strands twisted simultaneously.

[0015] Furthermore, the multiple strands of nickel-titanium alloy are twisted, the multiple strands of nickel-titanium alloy are combined into strands, both ends are tied and fixed with Kevlar fibers, and a mechanical clamp is used to fix the entire strand of fiber.

[0016] The effects achieved by the present invention are as follows: the present invention achieves high cooling efficiency and high durability by twisting the nickel-titanium alloy fiber, while the required stress input is relatively low. The twisting of the nickel-titanium alloy fiber produces a unique nonlinear stress gradient distribution, thereby forming a periodic rigid-flexible structure. The high stress area exhibits large entropy changes and temperature changes, while the low stress area exhibits high elastic recovery ability, and therefore has a large energy efficiency ratio and high efficiency. The twisting of the nickel-titanium alloy fiber can also prevent the generation and expansion of cracks, achieving a combination of high elastic-thermal properties and enhanced fatigue resistance. Its maximum fatigue endurance can reach 14752 cycles at a twist of 0.02 turns / mm and an elastic-thermal temperature span of 6K. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic illustration of elasto-thermal cycling for single (left) and multi-strand (right) NiTi fibers under twisting and untwisting.

[0018] Figure 2 Results of cyclic twisting / untwisting fatigue tests on single-strand and 3-strand NiTi alloy fibers, and cyclic stretching / recovery fatigue tests on the same fibers. (a) Average temperature change of NiTi alloy fibers during stretching / recovery cycles until failure. (b), (c) Average temperature change of 1-strand and 3-strand NiTi alloy fibers during twisting / untwisting cycles. The symbol × marks the fatigue failure point.

[0019] Figure 3 . Stress-strain curves of nickel-titanium alloy fibers subjected to 200 stretching / recovery cycles at different strains (a: 3.6%, b: 6.5%, c: 13%, d: 15.9%).

[0020] Figure 4 .Percent residual strain during cyclic stretching of NiTi alloy fibers under different applied stresses.

[0021] Figure 5 (a) Input work (open symbols) and hysteresis work (solid symbols) of NiTi alloy fiber during stretching / recovery cycle. (b) Dissipated energy of NiTi alloy fiber during cyclic stretching / recovery process.

[0022] Figure 6 .Relationship between torque and twist density of a single-strand nickel-titanium alloy fiber when subjected to 200 twisting / untwisting cycles at different twist densities (a: 0.02, b: 0.04, c: 0.06, d: 0.07 turns / mm).

[0023] Figure 7 .Residual twist percentage (ratio of residual twist density to applied twist density) of single-strand NiTi alloy fiber during cyclic twisting / untwisting at different applied torques.

[0024] Figure 8 (a) Input work (open symbols) and hysteresis work (solid symbols) of a single strand of NiTi alloy fiber during cyclic twisting / untwisting. (b) Dissipated energy of a single strand of NiTi alloy fiber during cyclic twisting / untwisting.

[0025] Fig. 9 Relationship between torque and twist density of three-strand nickel-titanium alloy fibers subjected to 200 twisting / untwisting cycles at different twist densities (a: 0.02, b: 0.04, c: 0.06, d: 0.07 turns / mm).

[0026] Fig.10 .Percentage of residual twist density during cyclic twisting / untwisting of three-ply NiTi alloy fibers at different applied torques.

[0027] Fig.11(a) Input work (open symbols) and hysteresis work (solid symbols) of three-ply NiTi alloy fibers during cyclic twisting / untwisting. (b) Dissipated energy of three-ply NiTi alloy fibers during cyclic twisting / untwisting.

[0028] Fig.12 . Low-magnification (left column) and high-magnification (right column) scanning electron microscopy (SEM) images of a fractured cross section of a NiTi alloy fiber after cyclic twisting / untwisting (top) and cyclic stretching / recovery (bottom).

[0029] Fig.13 .Results of cyclic stretch / recovery and twist / untwist tests. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0031] In the present invention, the nickel-titanium alloy used contains 51.3% nickel and 48.7% titanium by weight, and is processed into a fiber shape with a diameter ranging from 0.4mm to 1.0mm. The fixing method is to use a drill chuck to fix the two ends of the fiber. The driving method is to use a stepper motor to connect the fixed chuck to drive the nickel-titanium alloy fiber elastically and thermally. When the drill chuck is used to clamp the nickel-titanium alloy fiber, a 0.3mm copper foil is used to wrap the nickel-titanium alloy as a buffer layer at the contact point between the chuck and the nickel-titanium alloy. One of the drill chucks is fixed in a stable position, and the other drill chuck is coaxially connected to a stepper motor with a fixed length.

[0032] In the present invention, the austenite-martensite phase transition temperature of the nickel-titanium alloy is between -20 and 0°C, and the fiber length is between 3 and 30 cm.

[0033] As an embodiment of the present invention, the nickel-titanium alloy material is not limited to being twisted in one strand, and the twisted nickel-titanium alloy material also includes twisting 2 to 5 strands at the same time. When twisting multiple strands of nickel-titanium alloy material, the multiple strands of nickel-titanium alloy are combined into strands, and the two ends are fastened and fixed with Kevlar fibers, and the entire strand of fiber is fixed with a mechanical chuck.

[0034] As an embodiment of the present invention, the steps of cyclic elastic heating are as follows: 1) controlling the stepper motor connected to the nickel-titanium alloy fiber material to twist it at a rate of 5-50 turns / s, so that the nickel-titanium alloy generates heat; 2) exchanging heat with the environment until the temperature is close to the environment; 3) untwisting it at the same rate, so that the nickel-titanium alloy is cooled; 4) exchanging heat with the environment until the temperature is close to the environment. The above steps realize the cyclic cooling and heating of the nickel-titanium alloy.

[0035] Embodiment 1:

[0036] See attached Figure 1 , a method for improving elastic-thermal cycle durability by twisting nickel-titanium alloy fibers,

[0037] The method flow is shown in the following steps:

[0038] 1) Cutting a certain length and a certain number of strands of nickel-titanium alloy fiber;

[0039] 2) Wrap the two ends of the fiber with 0.3mm copper foil. If it is multi-strand, first wrap the nickel-titanium alloy fiber with copper foil, then wrap the copper foil with Kevlar fiber, and fix the two ends to the drill chuck;

[0040] 3) Fix the drill chuck to the stepper motor and set the motor spacing;

[0041] 4) Set the stepper motor operation program and constant temperature box temperature;

[0042] 5) Set the number of motor forward and reverse revolutions in a gradient manner, and the waiting time for each operation is 120s;

[0043] 6) Click to start the thermal imager and stepper motor at the same time to obtain real-time data of temperature changes;

[0044] 7) Set up the program to repeat the above steps to test the elastic and thermal properties of the nickel-titanium alloy fiber during fatigue.

[0045] Figure 1 A schematic illustration of the elasto-thermal cycle is shown for single (left) and multi-strand (right) NiTi fibers under twisting and untwisting. A stepper motor grips one end of a single or multi-strand NiTi fiber and rotates it to apply twist, which transforms the alloy fiber's austenite into martensite and generates heat. Reverse rotation untwistes the twist, causing the martensite to revert to austenite, absorbing heat from the environment in the process.

[0046] In view of the effects of the above embodiments of the present invention, the present invention performs the following tests.

[0047] Thermal-elastic cycling performance test using twisted nickel-titanium alloy fibers:

[0048] The present invention conducted a cyclic twisting / untwisting fatigue test on single-strand and three-strand nickel-titanium alloy fibers, and a cyclic stretching / recovery fatigue test on the same fibers as a control experiment. Figure 2, for a single-strand nickel-titanium alloy fiber, at a twist density of 0.03 turns / mm, the cycle life was 10548 cycles when the average temperature change (ΔT) upon heating was 5.4K; while near the breaking point, ΔT was -4.6K. When the twist density of the nickel-titanium alloy fiber increased to 0.07 turns / mm, the cycle life decreased to 3335 cycles, at which time the heating ΔT was 17.6K and the cooling ΔT was -10.9K. Next, the present invention studied the cyclic heating / cooling of three-strand nickel-titanium alloy fibers, with a cycle life of 4030 cycles at a twist density of 0.03 turns / mm, a heating ΔT of 7.4K, and a cooling ΔT of -6.8K. At a twist density of 0.07 turns / mm, the cycle life was 1552 cycles, with a heating ΔT of 17.8K and a cooling ΔT of -12.5K. In contrast, the cycle life of a single strand of NiTi alloy fiber under elasto-caloric heating / cooling (stretching / recovery) was 1163 cycles with a heating ΔT of 1.2K, a cooling ΔT of -1.2K, and an applied strain of 3%. At an applied strain of 9%, the cycle life remained at 1167 cycles with a heating ΔT of 9.0K and a cooling ΔT of -6K. As the number of torsional cycles increased from 1 to 1000, the single strand of NiTi alloy fiber maintained a nearly constant heating ΔT of 21.6K and cooling ΔT of -14.4K at a twist density of 0.07 turns / mm. In contrast, as the number of elasto-caloric cycles increased from 1 to 20, the heating ΔT of the NiTi alloy fiber decreased from 14.3K to 9.3K and the cooling ΔT decreased from -8.8K to -6.9K at a strain of 9%.

[0049] Figure 2 .(a) Average temperature variation of NiTi alloy fibers during stretch / recovery cycles until failure. (b), (c) Average temperature variation of 1-strand (b) and 3-strand NiTi alloy fibers during twist / untwist cycles. (d) Fatigue life as a function of twist density (top) and tensile strain (bottom). The symbol × marks the fatigue failure point. (a) Average temperature variation of NiTi alloy fibers during stretch / recovery cycles until failure. (b), (c) Average temperature variation of 1-strand and 3-strand NiTi alloy fibers during twist / untwist cycles. The symbol × marks the fatigue failure point.

[0050] Mechanical cyclic performance testing using twisted nickel-titanium alloy fibers.

[0051] 1) Evaluation indicators

[0052] During tensile loading and unloading, the input work (W i,ten W i,ten ) and hysteresis work (W h,ten W h,ten) are defined as the minimum mechanical work and ideal mechanical energy dissipation required to stretch the fiber to a specific strain; their expressions are:

[0053]

[0054] Here, σ represents the tensile stress, ε represents the tensile strain, V is the volume of the NiTi alloy fiber, and m NiTi is the mass of the NiTi alloy fiber. Correspondingly, the input work (W) during the torque-twist cycle i,tor ) and hysteresis work (W h,tor ) is defined as:

[0055]

[0056] Here, τ represents the applied torque and α represents the torsion angle. Dissipated energy (E dis ) is defined as the ratio of hysteresis work to input work (i.e. W h,ten / W i,ten or W h,tor / W i,tor ), which is related to the hysteresis loss. The present invention also defines the residual strain percentage (χ ten =ε r / ε,χ ten =ε r / ε) to evaluate the extent to which the NiTi alloy fiber can recover to its initial state after a stretching cycle; ε and ε r represent the tensile strain and residual strain, respectively.

[0057] 2) Cyclic mechanical properties test

[0058] Then, the present invention conducted cyclic mechanical tests on nickel-titanium alloy fibers, including stretching / recovery cycles until different strains and twisting / untwisting cycles until different twist densities. For the stretching / recovery cycles of nickel-titanium alloy fibers, obvious hysteresis was observed. The nickel-titanium alloy fibers exhibited significant residual strain during cyclic stretching. When mechanical stresses of 260, 520, 580 and 640 MPa were applied to the nickel-titanium alloy fibers, the strains of the filaments reached plateau values ​​of 1.2%, 3.6%, 8.5% and 15.9%, respectively, while the percentages of residual strain reached plateau values ​​of 63.2%, 50.2%, 17.2% and 86.6%, respectively ( Figure 4 ).

[0059] Next, the present invention calculates the input work, hysteresis work and dissipated energy (ratio of hysteresis work to input work) during the cyclic stretching process. Figure 3), the input work reached the platform values ​​of 1.68, 3.49, 5.88 and 5.53 J / g, the hysteresis work reached the platform values ​​of 0.37, 1.22, 4.38 and 2.94 J / g, and the dissipated energy reached the platform values ​​of 22.2%, 34.8%, 72.4% and 53.1%, respectively. Figure 5 ).

[0060] Single NiTi alloy fibers were subjected to cyclic mechanical testing, including twisting / untwisting cycles up to different twist densities.

[0061] Compared with the stretching / recovery cycle, the twisting / untwisting cycle showed less hysteresis and less residual deformation. The NiTi alloy fiber also showed a relatively small residual twist density during the cyclic twisting / untwisting process. For the applied torques of 0.037, 0.042, 0.067 and 0.081 N·m, the twist density reached the plateau values ​​of 0.03, 0.04, 0.06 and 0.07 turns / mm, respectively, while the percentage of residual torsion reached the plateau values ​​of 8.2%, 11.6%, 10.9% and 12.4%, respectively ( Figure 7 ).

[0062] Next, the input work, hysteresis work, and dissipated energy (ratio of hysteresis work to input work) during the twisting / untwisting cycle were calculated. Figure 6 ), the input work reached the platform values ​​of 2.1, 2.6, 4.1 and 3.8 J / g, the hysteresis work reached the platform values ​​of 0.11, 0.56, 0.95 and 0.88 J / g, and the dissipated energy reached the platform values ​​of 7.6%, 18.5%, 20.3% and 25.5% respectively ( Figure 8 ).

[0063] Cyclic mechanical testing of three-ply NiTi alloy fibers, including twisting / untwisting cycles up to different twist densities, was performed.

[0064] The three-strand NiTi alloy fiber also showed quite small hysteresis and residual twist density during cyclic twisting / untwisting. For applied torques of 0.1, 0.13, 0.21, and 0.26 N·m, the twist density reached plateau values ​​of 0.02, 0.04, 0.06, and 0.07 turns / mm, respectively, while the percentage of residual twist (the ratio of residual twist density to applied twist density) reached plateau values ​​of 7.9%, 15.6%, 15.0%, and 17.1%, respectively. Fig. 9 , Fig.10 ).

[0065] Next, the present invention calculated the input work, hysteresis work and dissipated energy (ratio of hysteresis work to input work) during the twisting / untwisting cycle of three-strand nickel-titanium alloy fibers. For the applied twisting densities of 0.04, 0.06 and 0.07 turns / mm, the input work reached the platform values ​​of 2.9, 4.0 and 4.4 J / g, respectively, the hysteresis work reached the platform values ​​of 0.51, 0.80 and 1.00 J / g, respectively, and the dissipated energy reached the platform values ​​of 16.7%, 19.7% and 22.2%, respectively ( Fig.11 ).

[0066] The fracture surfaces of NiTi alloy fibers after cyclic stretching / recovery and twisting / untwisting were studied by scanning electron microscopy (SEM).

[0067] After stretching / recovery cycles, the NiTi alloy fibers showed obvious radial pattern traces that originated at the edges of the cross section where stress was concentrated. The cross section showed small pits arranged along the radial traces, indicating the direction of fracture propagation.

[0068] For the cyclic twisting / untwisting of the NiTi alloy fiber, curved concentric circles extending from the center of the cross section to the edge are seen. No obvious crack initiation is observed in this case, suggesting that the crack growth and cross-sectional tearing mechanism is due to global structural damage accumulation caused by cyclic torsion rather than local fracture caused by cyclic strain ( Fig.12 ).

[0069] Superelastic nickel-titanium alloy fibers are mainly composed of austenite phase at room temperature. The crystallographic changes of nickel-titanium alloy fibers during tension and torsion cycles were studied by X-ray diffraction (XRD) characterization. The tests were carried out using a RigakuUltima IV X-ray diffractometer equipped with CuKα radiation; the scanning rate was 1° / min and the angle range studied was 40° to 45°. Wire samples with different fatigue histories were prepared, and the austenite B2 (110) diffraction peak was selected to analyze the composition of the wire samples. The crystallographic parameters are from the International Center for Diffraction Data (ICDD) database. The unit cell parameters are as follows: For austenite B2: For Martensitic B19: β=96.8°.

[0070] To calculate the austenite grain size D, the present invention uses the Scherrer equation:

[0071]

[0072] Here, λ is the wavelength of the X-ray source, K=0.89, β is the half-width at half maximum (FWHM) of the diffraction peak corresponding to the austenite (110) plane, and θ is the corresponding diffraction peak center angle. Fig.13The half-width at half maximum, grain size, and diffraction peak center angle of the austenite (110) plane during torsion and tension cycles are shown.

[0073] Fig.13 . (a)–(c) Full width at half maximum (FWHM) of the austenite (110) diffraction peak, (d)–(f) grain size, and (g)–(i) center position of the austenite (110) diffraction peak. These results correspond to the twisting / untwisting of a NiTi alloy fiber (a), (d), (g), the twisting / untwisting of three NiTi alloy fibers (b), (e), (h), and the stretching / recovery of a NiTi alloy fiber (c), (f), (i).

[0074] The present invention proposes a method for improving the elastic thermal fatigue durability of nickel-titanium alloy. First, a nickel-titanium alloy with a weight percentage of 51.3% nickel and 48.7% titanium is processed into a fiber shape with a diameter ranging from 0.4mm to 1.0mm, and then the fiber is wrapped at both ends with 0.3mm copper foil. If the nickel-titanium alloy fiber is multi-stranded, the nickel-titanium alloy fiber is first wrapped with copper foil, and then the copper foil is wrapped with Kevlar fiber, and the two ends are fixed to the drill chuck. A stepper motor is used to connect the fixed chuck to drive the nickel-titanium alloy fiber elastic thermal. Finally, the elastic thermal fatigue durability test of the nickel-titanium alloy is realized. Obvious hysteresis phenomenon was observed for the stretching / recovery cycle of the nickel-titanium alloy fiber. The nickel-titanium alloy fiber exhibits significant residual strain during the cyclic stretching process. When mechanical stresses of 260, 520, 580 and 640 MPa were applied to the nickel-titanium alloy fiber, the strain of the filament reached plateau values ​​of 1.2%, 3.6%, 8.5% and 15.9%, respectively, while the percentage of residual strain reached plateau values ​​of 63.2%, 50.2%, 17.2% and 86.6%, respectively. In the cyclic mechanical test of a single nickel-titanium alloy fiber, the twisting / untwisting cycle showed smaller hysteresis and less residual deformation compared with the stretching / recovery cycle, and the nickel-titanium alloy fiber also showed a relatively small residual twist density during the cyclic twisting / untwisting process. When the three-strand nickel-titanium alloy fiber was subjected to cyclic mechanical testing, the three-strand nickel-titanium alloy fiber also showed a relatively small hysteresis and residual twist density during the cyclic twisting / untwisting process. The highest fatigue endurance of the fiber reached 14752 cycles at a twist of 0.02 turns / mm and a thermal elastic temperature span of 6K. High cooling efficiency and high durability are achieved by twisting the NiTi alloy fibers, while requiring low stress input. Twisting the NiTi alloy fibers produces a unique nonlinear stress gradient distribution, resulting in a periodic rigid-flexible structure. High stress areas show large entropy changes and temperature changes, while low stress areas show high elastic recovery, resulting in a large energy efficiency ratio and high efficiency. Twisting the NiTi alloy fibers can also prevent the generation and expansion of cracks, achieving a combination of high elastic-thermal properties and enhanced fatigue resistance.

Claims

1. A method for improving the thermal fatigue durability of nickel-titanium alloy, characterized in that The following steps are involved: (a) The nickel-titanium alloy used contains 51.3% nickel and 48.7% titanium by weight and is processed into a fiber shape with a diameter ranging from 0.4 mm to 1.0 mm; (b) Use a drill chuck to fix both ends of the fiber; (c) using a stepper motor connected to a fixed chuck to drive the nickel-titanium alloy fiber elastic heat; Wherein step (b) is to wrap both ends of the fiber with 0.3 mm copper foil. If it is multiple strands, first wrap the nickel-titanium alloy fiber with copper foil, then wrap the copper foil with Kevlar fiber, and fix both ends to the drill chuck.

2. The method according to claim 1, characterized in that: The austenite-martensite phase transition temperature of the nickel-titanium alloy is between -20 and 0°C, and the fiber length is between 3 and 30 cm.

3. The method according to claim 1, characterized in that: When the drill chuck is used to clamp the nickel-titanium alloy fiber, a 0.3 mm copper foil is used to wrap the nickel-titanium alloy as a buffer layer at the contact point between the chuck and the nickel-titanium alloy.

4. The method according to claim 1, characterized in that: One of the drill chucks is fixed in a stable position, and the other drill chuck is coaxially connected to a stepper motor at a fixed length.

5. The method according to claim 1, characterized in that: The steps of cyclic elastic heating are as follows: 1) controlling the stepper motor connected to the nickel-titanium alloy fiber material to twist it at a rate of 5-50 turns / s, so that the nickel-titanium alloy generates heat; 2) exchanging heat with the environment until the temperature is close to the ambient temperature; 3) untwisting it at the same rate to cool the nickel-titanium alloy; 4) exchanging heat with the environment until the temperature is close to the ambient temperature. The above steps realize cyclic cooling and heating of the nickel-titanium alloy.

6. The method according to any one of claims 1 to 4, characterized in that: The twisted nickel-titanium alloy material further comprises 2 to 5 strands twisted simultaneously.

7. The method according to claim 6, characterized in that: The twisting of multiple strands of nickel-titanium alloy is that multiple strands of nickel-titanium alloy are combined into strands, both ends of which are fastened and fixed with Kevlar fibers, and the entire strand of fibers is fixed with a mechanical clamp.

8. The method according to claims 1-7, characterized in that: Its maximum fatigue durability reaches 14752 cycles at a twist of 0.02 turns / mm and a thermal-elastic temperature span of 6K.